Fundamentals of bone vasculature: specialization, interactions and functions - Owen-Woods, C; Kusumbe, A (Elsevier, 2021)
Angiogenesis, hematopoiesis and osteogenesis are fundamental processes mediating complex and essential biological functions. In the bone marrow, endothelial cells (ECs) are a principal mediator of regulatory signals that govern hematopoietic and mesenchymal stem cells. EC and osteoblast interactions and niche functions of ECs are fundamental in maintaining bone health and coordinating repair and regeneration following injury. These cellular interactions are subject to dysregulation and deterioration under stress, aging, chronic disease states and malignancy. Thus, the prospect of manipulating the bone vasculature has tremendous potential to advance therapeutic interventions for the management of bone diseases. This review discusses the current state of vascular-skeletal tissue interactions focusing on osteoblast and hematopoietic stem cells interaction with ECs.